OFFSET
0,3
COMMENTS
Let A(x) = (1 + k*x + (k-1)*x^2). Then the coefficients of (A(x))^2 sum to 4*k^2, where k = (n - 1). Examples: if k = 3 we have (1 + 3*x + 2*x^2)^2 = (1 + 6*x + 13x^2 + 12*x^3 + 4*x^4), and ( 1 + 6 + 13 + 12 + 4) = 36. If k = 4 we have (1 + 4*x + 3*x^2)^2 = (1 + 8*x + 22*x^2 + 24*x^3 + 9*x^4), and (1 + 8 + 22 + 24 + 9) = 64 = a(5). - Gary W. Adamson, Aug 02 2015
For n>0, a(n) are the Engel expansion of A197036. - Benedict W. J. Irwin, Dec 15 2016
LINKS
FORMULA
a(n) = A004275(n)^2. - M. F. Hasler, Jan 16 2012
a(n) = 4*(-1+n)^2 for n>1; a(n) = 3*a(n-1)-3*a(n-2)+a(n-3) for n>4; G.f.: x*(x^3-7*x^2-x-1) / (x-1)^3. - Colin Barker, Sep 15 2014
EXAMPLE
36 is in the sequence because 36 = 6^2 = 210 base 3 and 21 base 4 = 9 = 3^2.
MATHEMATICA
Join[{0, 1}, LinearRecurrence[{3, -3, 1}, {4, 16, 36}, 50]] (* Vincenzo Librandi, Aug 03 2015 *)
PROG
(PARI) concat(0, Vec(x*(x^3-7*x^2-x-1)/(x-1)^3 + O(x^100))) \\ Colin Barker, Sep 15 2014
(PARI) is_ok(n)=issquare(n) && issquare(floor(n/4));
first(m)=my(v=vector(m), r=0); for(i=1, m, while(!is_ok(r), r++); v[i]=r; r++; ); v; /* Anders Hellström, Aug 08 2015 */
(Magma) [Floor((2*n^2)/(1 + n))^2: n in [0..60]]; // Vincenzo Librandi, Aug 03 2015
CROSSREFS
KEYWORD
nonn,base,easy
AUTHOR
Henry Bottomley, Jul 14 2000
STATUS
approved